Needs Analysis : Media Development Genially-Based Interactive Infographics to Improve Student Literacy Teaching Environmental Issues in Junior High School - Dewanti, Amara; Hartono, Hartono; Syarifuddin, Syarifuddin (FKIP - Universitas Riau, 2025)
This study was motivated by the low effectiveness of conventional learning in improving students' literacy on environmental issues in junior high schools. The learning media used by educators tend to be monotonous and less interactive, thus not suitable for the characteristics of the digital generation. This study aims to analyze the need for developing interactive infographics based on Genially as an innovative solution in science learning. The method used was qualitative descriptive with interview techniques and questionnaire distribution to 5 educators and 100 students at SMP Negeri 16 Palembang. The results showed that educators experienced obstacles in using digital media, low learning interactivity, and difficulty explaining abstract concepts. Meanwhile, students showed high interest in visual media, communicative language, and technology-based learning. Needs analysis showed that the development of Genially-based interactive media is highly relevant for improving science literacy, active participation, and critical attitudes towards environmental issues. In conclusion, Genially-based interactive infographics have the potential to be an effective tool in creating engaging, contextual, and humanistic learning in line with the demands of 21st-century education.